A phase I dose escalation study of oral bexarotene in combination with intravenous decitabine in patients with AML. Issue 8 (28th April 2014) - Welch, John S.; Niu, Haixia; Uy, Geoffrey L.; Westervelt, Peter; Abboud, Camille N.; Vij, Ravi; Stockerl‐Goldstein, Keith E.; Jacoby, Meagan; Pusic, Iskra; Schroeder, Mark A.; Dipersio, John F.; Cashen, Amanda F.
<x xml:space="preserve">Abstract</x> The response rate of non‐M3 acute myeloid leukemia (AML) to all trans retinoic acid has been limited. Using Affymetrix expression arrays, we found that in diverse AML blasts RXRA was expressed at higher levels than RARA and that mouse Ctsg‐PML‐RARA leukemia responded to bexarotene, a ligand for RXRA. We therefore performed a phase I study of combination bexarotene and decitabine in elderly and relapsed AML patients. We found that this combination was well tolerated, although outcomes were modest (1 CRi, and 3 PR among 19 patients). Correlative studies found that patients with clinical response had increased differentiation to bexarotene both in vivo and ex vivo, suggesting that pre‐treatment analysis might identify a more susceptible subgroup of patients. Am. J. Hematol. 89:E103–E108, 2014. © 2014 Wiley Periodicals, Inc.